Hubungan Perilaku 3M Plus Dengan Kejadian Demam Berdarah Dengue (DBD) Di Wilayah Kerja Puskesmas Susunan Baru Kota Bandar Lampung Tahun 2024 - Tati Baina Gultom; Wibowo Ady Sapta; Bambang Murwanto; M. Alfath Bayu Putra (Pusat riset dan Inovasi Nasional, 2025)
Dengue Fever is a viral infection that spreads from mosquitoes to humans. In Susunan Baru Health Center, the number of dengue cases increased by 55% in 2024. Mosquito nest eradication (PSN) with 3M Plus combination, fogging, and community service can reduce the breeding of Aedes mosquitoes and reduce Dengue Fever. The purpose of this study was to determine the relationship between 3M plus behavior and Dengue Fever in Susunan Baru Health Center, Bandar Lampung City. This method is quantitative research, case control study. The sample was 128 samples, 64 case respondents and 64 control respondents (1:1). Case samples were taken with total sampling technique, control samples were taken with purposive sampling technique. Data analysis was conducted with chi-square test (α)=0.05. Conclusion There is a significant relationship between closing water reservoirs (p value = 0.000), draining water reservoirs (p value = 0.003), recycling used goods (p value = 0.000), changing flower vase water (p value = 0.000) and sprinkling larvicide powder (p value = 0.036) with the incidence of Dengue Fever in the Susunan Baru Health Center Working Area, Tanjung Karang Barat Subdistrict, Bandar Lampung City. Keywords: Aedes, DBD, Dengue Fever, PSN, 3 M Plus.